Pediatric pulmonology, asthma, and sleep medicine : a quick reference guide - American Academy of Pediatrics. Section on Pediatric Pulmonology and Sleep Medicine; Stokes, Dennis C.; American Academy of Pediatrics (Itasca, IL : American Academy of Pediatrics, 2018)
Obtain practice-focused guidance on the diagnosis, evaluation and treatment of the most commonly encountered pediatric respiratory conditions, asthma-related difficulties, and sleep disorders -- Back cover.
Includes bibliographical references (pages 857-860) and index.
Keywords: Pediatric respiratory diseases; Sleep disorders in children; Infant; Child; Infant; Respiratory Tract Diseases; Sleep Wake Disorders; Pediatric respiratory diseases; Sleep disorders in children; Handbook